The 2011 Libyan uprisings and the struggle for the post-Qadhafi future - Pack, Jason 1980- (Palgrave Macmillan, 2013)
The 2011 LibyanUprisings is a thematic investigation of howpre-existing social, regional, tribal, and religious fissures influenced thetrajectory of the 2011 Libyan Uprisings and an analysis of what this means for thepost-Qadhafi future